Pengaruh Pemberian Vitamin C Dosis Tinggi Terhadap Kadar Tumor Necrosis Faktor Alfa Pada Aktivitas Fisik Berat: Studi Eksperimental Pada Tikus Galur Wistar Jantan - Trisnadi, Reza Adityas; Sundawa, Angga Pria (Sultan Agung Islamic University of Semarang, 2022)
ABSTRACT Strenuous physical activity will cause fatigue in athletes so it will be easier to experience infection. Strenuous physical activity will cause fatigue in athletes so it will be easier to experience infection. This condition in its prevention requires exogenous antioxidants such as vitamin C that reduce ros production. Vitamin C acts as a companion factor in several enzymatic reactions in the body and can boost components of the immune system so that it is expected to lower TNF-α levels. This type of research is an experimental laboratory with a post test only control group design approach using animals to try male white rats with malnutrition conditions that meet the criteria of inclusion and exclusion. The study plan was conducted for ± 22 days. The results of this study are expected to develop the use of high-dose vitamin C as an antioxidant to improve immune function or the immune system for the health of the body. Administering vitamin C at doses of 18 mg / ml / day and 36 mg / ml / day can reduce the amount of TNF-α in male rats who were given heavy physical activity.